Temporal Probability Analysis of Flood Occurrence Using Peak Over Threshold Method for Extreme Rainfall Events - Oktaviana Pratnya Paramitha; Syafei Arie Dipareza; Kuswanto Heri; Hermana Joni (BIO Web of Conferences)
Extreme rainfall often leads to flooding in various regions. This study conducts the analysis of temporal probability of flood risk due to extreme rainfall in Jakarta by using data from meteorological stations in Kemayoran (for Central Jakarta) and Tanjung Priok (for North Jakarta) over 30 years (1994-2023). Peak Over Threshold (POT) approach was applied to identify extreme rainfall events. Mean Residual Life Plot (MRLP) was used to determine thresholds for extreme rainfall, resulting in thresholds of 122 mm/day for Central Jakarta and 126 mm/day for North Jakarta. Using Generalized Pareto Distribution (GPD) modeling, the probability of flooding due to extreme rainfall exceeding these thresholds was calculated for various time frames. In Central Jakarta, the probability of flooding due to extreme rainfall exceeding 122 mm/day is 32.10% over 5 years, increasing to 97.90% over 50 years. In North Jakarta, the probability of flooding due to extreme rainfall exceeding 126 mm/day is 21.80% over 5 years and rises to 91.50% over 50 years. Extreme rainfall tends to result in higher probabilities of flooding over the long term. The results suggest that while extreme rainfall events are rare, it can cause the probability of flood occurrence to increase significantly over time.